Constraining primordial magnetic fields through large scale structure - Kahniashvili, Tina; Maravin, Yurii; Natarajan, Aravind; Battaglia, Nicholas; Tevzadze, Alexander G. (My University, 2013)
We study primordial magnetic field effects on the matter perturbations in the universe. We assume magnetic field generation prior to the big bang nucleosynthesis (BBN), i.e., during the radiation-dominated epoch of the universe expansion, but do not limit analysis by considering a particular magnetogenesis scenario. Contrary to previous studies, we limit the total magnetic field energy density and not the smoothed amplitude of the magnetic field at large (of the order of 1 Mpc) scales. We review several cosmological signatures, such as halo abundance, thermal Sunyaev-Zel'dovich (tSZ) effect, and Lyman-α data. For a cross-check we compare our limits with that obtained through the CMB faraday rotation effect and BBN. The limits range between 1.5 nG and 4.5 nG for n[subscript B]∈ in (– 3; –1.5).
Keywords: Primordial magnetic fields; Early universe; Large scale structure